Factors influencing return to work after stroke: the Korean Stroke Cohort for Functioning and Rehabilitation (KOSCO) Study - Junhee Han; Hae In Lee; Yong-Il Shin; Ju Hyun Son; Soo-Yeon Kim; Deog Young Kim; Min Kyun Sohn; Jongmin Lee; Sam-Gyu Lee; Gyung-Jae Oh; Yang-Soo Lee; Min Cheol Joo; et al. (BMJ Open)
Objective To investigate the rate of return to work and identify key factors associated with return to work between 3 months and 2 years after stroke.Design Prospective cohort study.Setting The Korean Stroke Cohort for Functioning and Rehabilitation (KOSCO) in Korea.Participants A total of 193 persons with first-ever stroke who reported working status at 3 months after stroke.Outcome measures Data on baseline characteristics were collected from medical records. Functional assessments were performed using the National Institutes of Health Stroke Scale, the modified Rankin Scale, the Fugl-Meyer Assessment, the Functional Ambulatory Category, the Korean Mini-Mental State Examination, the Korean version of the Frenchay Aphasia Screening Test, the American Speech-Language-Hearing Association National Outcomes Measurement System, the Korean-Modified Barthel Index, the Geriatric Depression Scale-Short Form and the EuroQol-5 dimensions. An enumeration survey included the Reintegration to Normal Living Index, the Psychosocial Well-being Index-Short Form , the Family Support Index and the Caregivers Burden Index.Results Overall, 145 (75.1%) patients who had a stroke in the Continuously-Employed group and 48 (24.9%) in the Employed-Unemployed group returned to work between 3 months and 2 years after stroke. Multivariate logistic analysis demonstrated that in patients who had a stroke, characteristics such as age, PWI-SF Score, and caregiver characteristics, including age, sex (female) and living arrangements, were significantly associated with return to work between 3 months and 2 years after stroke.Conclusion Age and PWI-SF Score of patients who had a stroke, as well as the age, sex and living arrangements of caregivers, are key factors influencing the return to work after stroke.Trial registration number NCT03402451.